Geleneksel Diplomasiden Siber Diplomasiye Geçiş: Aktörler ve Süreçler - ORHON, Özgün (Cyberpolitik Journal, 2023)
With the globalization process and the developments in information and communication technologies, there is a structural change in the way of carrying out and presentation of diplomacy, which is under the influence of the internet and social media. Cyberspace provides digital/cyber tools that are distinct from traditional diplomatic activities, allowing for more effective implementation of diplomatic relations, therefore, developments in cyberspace forces diplomatic activities to this path. This has led to the emergence of cyber diplomacy which significantly alters diplomatic practices, the ways in which diplomacy is practiced, the methods and tools of diplomacy. In this article, the actors and transformations of diplomacy from traditional diplomacy to cyber diplomacy, the methods and tools applied in diplomacy in the process of evolution from traditional diplomacy to cyber diplomacy will be examined.